Ranking Indonesian Listed Banks on Its Corporate Social Responsibility Disclosures - Ratnawaty Tandanu; Daryanto Hesti Wibowo (Bina Nusantara University, 2008)
In Indonesia, corporate social responsibility (CSR) is a new concept and companies have been pressurized to include corporate social responsibility as part of strategic management to sustain competitive advantage. The main objective of this study is to evaluate the level of CSR disclosures in Indonesian listed banks’ annual reports. In addition, the writer observes the kind of CSR activities currently implemented by the banks. Subsequently, the writer tries to discover regulations pertaining to recording CSR disclosures. Method use Examines social responsibility information disclosures on the 2004 – 2006 annual reports using content analysis through detecting the presence or absence of social responsibility information. The result generated from this study is the ranking of CSR disclosures among Indonesian listed banks according to several categories. Moreover, the levels of disclosures, as well as the kind of CSR activities carried out by Indonesian listed banks were listed. Conclusion is- Generally, banks with higher total assets and net income as well as state-owned disclose more than banks with lower total assets, lower net income, and private-owned. There are still a lot of room for improvements in terms of CSR disclosures especially in environmental issues like lending and investment policies and conservation of natural resources and recycling activities as banking industry consume vast amounts of resources like paper and energy and create waste.